DOĞUMDA BAKILAN UMBİLİKAL KORDON KAN GAZI DEĞERLERİNİN ÖNEMİ - BENİAN, Ali and ULUDAĞ, Seyfettin and ATIŞ, Alev and GÖK, Murat and MADAZLI, Rıza (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Analysis of umbilical cord blood acid-base status at birth could give some information about the fetal intrapartal condition retrospectively. Normally umbilical cord arterial blood reflects fetal acid-base balance and umbilical cord venous blood reflects a combination of maternal acid-base status and placental function. In this study we aimed to demonstrate the relationship between the umbilical cord gas parameters and fetal well-being as well as to assess the usefulness of routine umbilical cord blood sampling. During a 12-month period we made the umbilical cord arterial and venous blood gas analysis of 199 healthy pregnant women between the 37th and 42nd week of gestation. During the trial all samples were taken by the same trained midewife and nurse. Immediately after each birth, the umbilical cord was clamped twice about 10 cm apart.Blood was taken first from the artery and from the vein using preheparinised syringes. Analysis was achieved within 30 minutes of delivery. Tracings indicative of fetal acidosis were defined as persistent late decelerations and severe variable decelerations (heart rate dropping to <70 beats/min and lasting >60 seconds). Results.- We classified the deliveries as normal (head or breech presentation with or without induction) and operative (Cesarean section, vacuum and forceps deliveries) to compare the fetal blood parameters. Each group was evaluated for the existence of intra-uterine growth retardation and fetal weight at delivery separately. Umbilical cord arterial pH, PO2 and venous pH, pCO2, pO2 difference between normal deliveries and operative deliveries done for fetal distress were statistically significant (p<0.05). Conclusion.- We conclude that umbilical cord blood pH and gases should be obtained only in cases of high risk pregnancies and in depressed newborns so that the diagnosis of neonatal asphyxia could be excluded in 80% of the cases.